Identification of Phytochemical Compounds Antioxidant Leaf Extract and Clove Flower Extract (Syzygium aromaticum) - Adeleyda M. W. Lumingkewas; Adrien Jems Akiles Unitly (Jurnal Penelitian Pendidikan IPA, 2023)
One plant known as a flavoring spice, but also as a traditional medicinal plant that is thought to contain antioxidant phytochemical compounds, namely cloves (Syzygium aromaticum) which are widely found in Maluku, Sulawesi and surrounding areas. This study aims to identify the phytochemical compounds of antioxidants of leaf extract and clove flower extract (Syzygium aromaticum) originating from North Sulawesi using leaf methanol extract and clove flowers, where the test was carried out at the Research Center for Spice and Medicine Plant (Ballitro) Bogor included the alkaloid qualitative test , flavonoids, saponins, tannins, and triterpenoids. The results found that there were components of antioxidant phytochemicals in the form of alkaloids, flavonoids, saponins, tannins and triterpenoids in the extraran methanol leaf and clove flowers, with the frequency of existence ranging from there to many.